Analysis of changes in circular RNA expression and construction of ceRNA networks in human dilated cardiomyopathy. Issue 5 (22nd January 2021) - Lin, Zhenhao; Zhao, Yongchao; Dai, Fangjie; Su, Enyong; Li, Fuhai; Yan, Yan
Abstract: Dilated cardiomyopathy (DCM) is a severe life‐threatening disease worldwide, and the underlying mechanisms remain unclear. Circular RNAs (circRNAs) have been reported to play important roles in various cardiovascular diseases and can function as competitive endogenous RNAs (ceRNAs). However, their role in human DCM has not been fully elucidated. In the present study, heart samples from DCM patients and healthy controls were used to identify circRNAs by RNA sequencing. Real‐time quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was conducted to validate differentially expressed circRNAs and mRNAs. A total of 9585 circRNAs and 22050 mRNAs were detected in the two groups. Overall, 213 circRNAs and 617 mRNAs were significantly up‐regulated in the DCM group compared with the control group. Similarly, 85 circRNAs and 1125 mRNAs were significantly down‐regulated. According to the ceRNA theory, circRNAs can indirectly interact with mRNAs by directly binding to microRNAs (miRNAs), and circRNAs and mRNAs should be concurrently either up‐regulated or down‐regulated. Based on this theory, we constructed two circRNA‐miRNA‐mRNA networks by using the RNA sequencing data and prediction by proprietary software. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to probe the potential functions of differentially expressed circRNAs. In conclusion, this study revealed that the expression of cardiac circRNAs was altered in human DCM and explored the potential functions of circRNAs by constructing ceRNA networks. These findings provide a foundation for future studies of circRNAs in DCM.